The relationship between customer satisfaction, brand image and customer loyalty from the perspective of proton’s customers - Yeoh, Hooi Chin (2010)
The objective of this study was determine the relationship between the customer satisfaction (perceived product quality, perceived service quality and perceived price fairness) and customer loyalty in order to identify whether perceived product quality, perceived service quality and perceived price fairness have any significance effect on the loyalty of customer. In addition, the moderating effect of brand image on the relationship of customer satisfaction and customer loyalty also had been investigate to see if there were any significance effect on the relationship to different level of brand image. Questionnaire was the main instrument for this study. The data obtained were analyzed using multiple regression and hierarchical multiple regression analysis. The findings from this study showed that only the perceived product quality and perceived price fairness have significance effect on effect on the loyalty of customer. In the other words, customers will continue loyal or retain to Proton if they satisfy with the price and quality of automobile. This study also revealed that the brand image is serves as a moderator in affecting the relationship between customer satisfaction and loyalty.